An Evaluation Of The Classroom Teaching Knowledge And Skills Of Preservice Teachers In The Bachelor Of Teaching Programme - Linda, Liang Peng Yaep (2013)
This study aims to evaluate the classroom teaching knowledge and skills of preservice teachers in the Bachelor of Teaching Programme, an ongoing training programme in Teacher Education Institutes designed specifically for training preschool and primary school teachers. The preservice teachers will be awarded a degree upon their completion of the programme. The outcome evaluation is the primary focus of this study. The Malaysian Teacher Standards mapped onto an effective teaching framework forms the benchmark for this evaluation research. The process evaluation is the secondary focus of the study. Two particular predictors consisting of the opportunity to learn in the active learning environment and quality of practicum supervision were examined. The data collection adopted a survey methodology through the administration of questionnaires to elicit feedback from 641 respondents on their preparedness in classroom teaching and the two predicting factors of the programme. The participants comprised preservice teachers who were in their final semester of study. Classroom observations were also conducted to support the findings from the survey on the outcome of the programme. The findings from this study suggest that preservice teachers were well-prepared in all components of planning and preparation except for the component of designing pupil assessment where they were identified as only prepared. The preservice teachers were also weak in planning instructional groups. Interestingly, this study also reveals that the preservice teachers were well-prepared in all components of the classroom environment domain, a domain reputed to pose difficulties to preservice teachers in many other similar studies. The results of this study also indicate that preservice teachers were well-prepared in the component of communicating with pupils for the instruction domain. However, though the preservice teachers were found to be prepared in other components of the instruction domain, they were relatively weak in using assessment in instruction, using quality questions, using instructional groupings to ensure the success of lesson outcomes and making lesson adjustments. On the whole, the findings attest that the preservice teachers were well-prepared in classroom teaching. The opportunity to learn in the active learning environment and quality of practicum supervision were both predictors of the preservice teachers’ preparedness with the former being the stronger one. Further emphasis on assessment, using quality questions, groupings of pupils and learning adjustments during practicum supervision, microteaching, teacher induction programme and through curriculum review could enhance the preservice teachers’ classroom teaching knowledge and skills.